Electrochemical Characterization of Different Layers of Composite Incorporated Hot-Dip Zinc Coating - Arunima, S.R. (Asian Journal of Chemistry, 2020)
The present study beneficially explores nano TiO2 incorporated hot-dip zinc coatings for the enhanced corrosion protection of steel. Various electrochemical analyses such as open circuit potential (OCP), electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization studies were adopted to evaluate the enhanced galvanic performance and the stability of nano TiO2 composite incorporated coatings. The low corrosion current density and high polarization resistance of tuned composition of TiO2 incorporated hot-dip zinc coatings confirm its enhanced galvanic and corrosion resistant properties. The enhanced performance of TiO2 incorporated zinc coating was attributed to the combined effect of barrier and sacrificial behaviours.